PROSPECTIVE COMPARATIVE STUDY TO EVALUATE THE EFFICACY AND TOLERABILITY OF SERTRALINE WITH METHYLCOBALIN AND PREGABALIN WITH METHYLCOBALIN IN THE TREATMENT OF DIABETIC NEUROPATHIC PAIN - Dr.E.MANIVANNAN,M.D.; Dr.V.SIVASANKARI,M.D.; Dr.S.P.PRIYADARSINI,M.D. (International Journal of Pharma and Bio Sciences, 2016)
Different classes of medications like tricycle antidepressants, anticonvulsants, serotonin and norepinephrine reuptake inhibitors, opioids are used in the management of diabetic peripheral neuropathic pain. The studies on sertraline as an alternative to the above drugs are very minimal, hence an effort was made to compare with pregabalin. The aim of the study was to evaluate the efficacy and tolerability of two combinations (sertraline with methylcobalin and pregabalin with methylcobalin) in the treatment of diabetic eripheral neuropathy. This is a prospective, comparative single blind trial conducted in a tertiary care hospital and 100 patients were provided with above two combinations with 50 patients in each group. The primary efficacy endpoint was change in the mean pain score based on neuropathic pain scale. The secondary end points included Michigan neuropathy screening instrument. Routine local and systemic examination was done with the recording of adverse events. Relevant laboratory investigations were also recorded. Sertraline and methylcobalin were matched with pregabalin and methylcobalin in all the characteristics like demographic details and pain scoring scale. As far as the primary outcome was concerned, there was marked improvement in the pain relief, especially sharp pain, dull pain and cold pain seen in pregabalin group. Also a considerable improvement in symptomatology was noted in sertraline group. Thus, this study promised a hope for sertraline a SSRI in the treatment of diabetic peripheral neuropathy as a third choice if the other classes of drugs failed. To conclude, multiple studies have demonstrated the efficacy and safety of pregabalin with methylcobalin group. However, the rationale of combining sertraline with methylcobalin was tried in this study.